Triple and quadruple cervical artery dissections: a systematic review of individual patient data - Guglielmi, Valeria; Kloss, Manja (Journal of neurology, 2019)
Background and purpose: Simultaneous dissection of three or four cervical arteries rarely occurs. As a result, limited information is available on clinical characteristics, underlying causes, treatment, and outcome of these patients. Methods: We performed a systematic review of individual patient data on triple and quadruple cervical artery dissection (CeAD). We included all cases for whom, at minimum, data on age, sex and affected cervical arteries were available. Results: Out of 1396 publications identified in the initial search, 52 were included, with data available on 96 patients. Mean age was 42 years and 66% were women. 63% had triple CeAD. The most common manifestations were headache (69%), neck pain (44%), motor deficit (36%), and Horner syndrome (34%). 57% had an ischemic stroke, in the majority of these patients the stroke was confined to the vascular territory of a single artery. 83% were managed medically (antiplatelets or anticoagulants) and 11% underwent endovascular treatment. An underlying disease or triggering event was identified in 71%, most commonly trauma (35%, cervical manipulative therapy in 13%), infection (18%), fibromuscular dysplasia (16%), and hereditary connective tissue disorder (8%). In-hospital mortality was 1%. 80% of patients had a good functional outcome (mRS 0-1) at follow-up. Two recurrences (3%) were reported. Conclusions: Triple or quadruple CeAD mostly affected young women, and underlying disease or triggering event could be identified in more than two-thirds of patients. Less than two-thirds of triple or quadruple CeAD patients suffered ischemic stroke. Most patients were managed medically and the majority had a favorable outcome.